THE INTERACTION BETWEEN PHONETICS AND MORPHOLOGY IN ENGLISH (Modern education and development, 2025)
Phonetics and morphology are fundamental aspects of linguistics that, though often studied independently, are deeply intertwined in shaping the structure of a language. Phonetics is concerned with the sounds used in speech, investigating how they are produced, transmitted, and perceived, while morphology examines the internal structure of words, focusing on how smaller meaningful units, known as morphemes, combine to form complex words and phrases.